2008
DOI: 10.1002/art.23992
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rheumatoid arthritis with a syk kinase inhibitor: A twelve‐week, randomized, placebo‐controlled trial

Abstract: Objective. Spleen tyrosine kinase (Syk) has been identified as an important modulator of immune signaling in B cells and cells bearing Fc␥-activating receptors. R788, a prodrug of active metabolite R406, has been shown to be an inhibitor of Syk kinase, active in a variety of in vitro and in vivo models, suggesting potential activity in the treatment of rheumatoid arthritis (RA).Methods. We enrolled 189 patients with active RA despite methotrexate therapy in a 3-month, multicenter, ascending-dose, double-blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
257
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(282 citation statements)
references
References 17 publications
15
257
0
4
Order By: Relevance
“…In clinical trials Syk inhibitions was effective in immune thrombocytopenic purpura 54 and rheumatoid arthritis. 19,20 In summary, we demonstrate that pharmacological Syk inhibition targets several key events of GvHD pathogenesis including expansion and migration of Tcs as well as costimulation by and migration of DCs. Importantly, cytolytic effector function of cytotoxic T lymphocyte against leukemia cells and anti-MCMV immunity were preserved despite Syk inhibition.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In clinical trials Syk inhibitions was effective in immune thrombocytopenic purpura 54 and rheumatoid arthritis. 19,20 In summary, we demonstrate that pharmacological Syk inhibition targets several key events of GvHD pathogenesis including expansion and migration of Tcs as well as costimulation by and migration of DCs. Importantly, cytolytic effector function of cytotoxic T lymphocyte against leukemia cells and anti-MCMV immunity were preserved despite Syk inhibition.…”
Section: Discussionmentioning
confidence: 73%
“…18 Recent phase II clinical trials demonstrated that Fostamatinib treatment effectively improved response rates in patients with rheumatoid arthritis. 19,20 Therefore, by using pharmacological inhibitors we aimed to delineate the relevance of Syk with respect to protection from GvHD, graft-versus-leukemia effects and anti-viral immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse events included diarrhea, increase in systolic blood pressure, and neutropenia (24,39). RA is a disease with complex pathogenic mechanisms involving several inflammatory cascades and recruitment of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, a phase II clinical trial employing the SyK inhibitor, fostamatinib (R406), was shown to improve clinical responses without untoward serious side-effects [15]. From a pathophysiological perspective, R406 also reduced interleukin-6 (IL-6) and matrix metalloproteinase-3 levels in the serum of RA patients compared to the placebo arm [16].…”
Section: Spleen Tyrosine Kinase (Syk)mentioning
confidence: 99%